XELOX in colorectal cancer: a convenient option for the future?. (February 2011) - Lindsay, Colin R; Cassidy, Jim
XELOX is a 3-weekly chemotherapy combination of oral capecitabine and intravenous oxaliplatin. The central hypothesis that led to its development was that it would provide a convenient and cost-effective alternative to intravenous fluorouracil-based chemotherapy doublets, without compromising on anti-tumor efficacy. Recently its role in colorectal cancer has become more established in both the metastatic and adjuvant setting. Ongoing investigation of XELOX continues in a number of directions: its combination with novel biological agents, its efficacy and safety in the elderly, and the development of biomarkers that can predict its anti-tumor effect. This article provides a comprehensive and up-to-date synopsis of all pertinent clinical studies detailing this regimen and its promise for the future.